Argentophilic Hydrogen Ferrocyanide Electrodes for Robust Electrokinetic Flow in a Non-Gassing Pump. Issue 8 (24th May 2016) - Mathi, Selvam; Nagarale, Rajaram K.
Abstract : The present study reports a non-gassing and non-contaminating electrode material and its characterization for potential applications in a microfluidic device such as insulin pump. An electroosmotic pump was assembled by sandwiching a silica membrane between two flow-through argentophilic hydrogen ferrocyanide electrodes made up of ascorbate reduction of silver ferricyanide (cathode) and silver ferrocyanide (anode). This assembly generated a electroosmotic flux of 80 μL/min/cm 2 with the application of 1 V across the cell. The flow increased linearly with the applied voltage. Passage of 0.7 C resulted 2.7 mL of water flow. This is equivalent to flow of 2.1 × 10 4 water molecules for the passage of each electron. This is the high performance electrode material reported for non-gassing, non-contaminating and low voltage electroosmotic pump in the literature with stall pressure of ∼2 kPa at 1 V applied voltage. The pump operates exclusively by electro-oxidation of hydrogen ferrocyanide at anode and electro-reduction of polymeric prussian blue analogue at cathode.